Effect of Organic Fertilizer on Growth and NPK Uptake of Dayak Onion Cultivated on Inland Peat Soil - Syahid, Abdul; Atikah, Titin Apung (PLANTA TROPIKA, 2026)
Peatlands have the potential to support sustainable agricultural production when properly managed, particularly through the use of organic inputs. This study aimed to evaluate the effects of organic fertilizer on the growth and nitrogen, phosphorus, and potassium nutrient uptake efficiency of Dayak onion plants cultivated in inland peat soil. The research was conducted from September to December 2023 at the Experimental Garden of the Faculty of Agriculture at the University of Palangka Raya. A randomized block design was used with five levels of cow manure application: 0, 5, 10, 15, and 20 t.ha-1, each replicated four times. The application of cow manure significantly increased leaf number at 50, 60, and 70 days after planting (DAP), as well as the increase in leaf number between 40 and 50 days, root and shoot fresh weight, number of tillers, and fresh bulb weight. The 10 t.ha-1 treatment increased leaf number by 87% at 50 DAP, 74.2% at 60 DAP, and 43.8% at 70 DAP compared to the control treatment. However, it did not significantly affect plant height. The regression equation is y = −0.0081x² + 0.2226x + 2.8726, with R² = 0.99. The dose of cow manure fertilizer that produces maximum tuber fresh weight is approximately 13.75 t ha⁻¹. This dose shows the best growth response before tuber weight decreases at higher fertilization levels. These findings indicate that applying organic fertilizer, particularly at an optimal dosage, can improve the productivity of Dayak onion grown in peat soil, supporting the sustainable use of marginal land for horticultural development.